Dializno zdravljenje otrok in mladostnikov s končno ledvično odpovedjo - Novljan, Gregor (Medicinski razgledi, 2005)
Although chronic kidney disease (CKD) is not a typical disease of childhood and its frequency in children is much lower than in adults, it is neverthelessan important health problem in children and adolescents. Based on glomerular filtration rate (GFR), chronic kidney disease is dassified into five stages. The fifth stage of chronic kidney disease is also called terminalrenal failure (TRF). Children with chronic kidney disease require chronic substitution treatment. The types of substitution treatment include hemodialysis, peritoneal dialysis and renal transplantation. The incidence of newly discovered children with chronic kidney disease in Slovenia is 7 to 9 per million children a year. The most common causes of chronic kidney disease in small children are hypoplastic or dysplastic kidneys and hereditary nephropathy. ln older children and adolescents, glomerulonephritis (primarily focal segmental glomerulosclerosis) and pyelonephritis are at the forefront. Hemodialysis is a safe and effective method for chronic substitution treatmentin children, and good vascular access is of crucial importance for it, while in small children, peritoneal dialysis is chosen more frequently. Animportant advantage of peritoneal dialysis lies in the fact that patients can do it at home. In addition to dialysis treatment, children with chronic kidney disease also need extensive supportive treatment. Care should be taken to ensure adapted nutrition and appropriate growth and development, as well asto treat anemia, control the metabolism of calcium and phosphate, and regulate blood pressure.
Keywords: Kidney Failure, Chronic; Ledvica, odpoved kronična; Hemodialysis; Peritonealna dializa; Peritonealna dializa dolgotrajna, ambulantna; Peritoneal Dialysis; Peritoneal Dialysis, Continuous Ambulatory; Adolescenca; Child; Otrok; hemodializa; Adolescence; kronična ledvična odpoved; ledvične bolezni; otroci; mladostniki